Strengthening Solidarity to Enhance the Role of New University Students in Community Engagement - Saputra, Harius Eko; Yusuarsono, Yusuarsono; Yanto, Yanto; Imanda, Antonio (Indonesia Berdaya, 2021)
This article discusses the importance of the role of new university students in community engagement and how solidarity can be strengthened to support their social character development. New students often face difficulties in adjusting to the university environment, which can lead to social alienation and a lack of understanding of their roles as agents of change. Through a designed community service program, known as "Malam Keakraban" (Makrab), new students are invited to participate in activities that emphasize social interaction and value reflection. This program involves thematic discussions, collaborative games, and participatory learning aimed at building social awareness and solidarity among students. The results of this activity indicate an increase in active participation, initiatives to engage in social activities, and positive changes in communication patterns among students. Thus, this article emphasizes that strengthening solidarity among new students is a strategic step in shaping their character and enhancing their contributions to society.